(untitled) (Journal of Nepal Geological Society, 2023)
Urbanization is rapidly growing throughout the world, especially in the least developed and developing countries necessitating proper land use planning. However, the lack of sufficient study has created the possibility of unprecedented geohazards. In this study, a detailed geological and engineering geological mapping along with the geotechnical analysis of soils and sediments from the Bhainsepati–Pharsidol area of Lalitpur District has been carried out. Detailed geological maps and geological cross-sections were prepared on the scale of 1:25,000 following the most adopted stratigraphy of central Nepal for both hard rocks and Quaternary deposits. Two mappable geological units like the Tistung Formation and the Chandragiri Limestone of the Phulchauki Group are found within the hard rock succession at the study area’s hill sections. Similarly, the Quaternary succession is mapped into the Lukundol Formation and the Chapagaon Terrace deposits of Kathmandu Valley sediments from older to younger succession respectively. There is a distinct erosional unconformity between the rocks of the Phulchauki Group and the Quaternary Valley sediments. A kinematic analysis of discontinuities developed in the rocks was carried out in the rock slopes found in the area. Both field and laboratory analyses of soil samples were carried out for the representative samples. The laboratory tests include moisture content, specific gravity, particle size distribution, soil consistency, compaction, and consolidation properties. Finally, an engineering geological map was prepared on the same scale as geological mapping showing the details of the distribution of geo-materials. This study is expected to be valuable to make proper land-use decisions for town planning and developmental activities in the rapidly growing city of Nepal.